Thyroid Autoantibodies in Type -1 Diabetic Mellitus Patients and their Correlation with Thyroid function and Tumor Necrotic Factor-Alpha - Shnawa, Bushra Hussain; Taha, Abdulsameea Majeed (Science Journal of University of Zakho, 2023)
Type 1 Diabetes Mellitus (T1DM) is a complicated autoimmune disorder initiated by T-cell-mediated damage of pancreatic beta cells, resulting in insulin deficiency and the development of hyperglycaemia. This disease is most common in childhood and adolescence and frequently co-occurs with other autoimmune conditions like autoimmune thyroiditis. This work aimed to investigate thyroid autoantibodies and their correlation with thyroid functions and tumour necrosis factor-alpha (TNF-α) in T1DM patients. Eighty participants were enrolled in a case-control study, including sixty T1DM patients and twenty healthy controls. Peripheral blood specimens were taken from individuals with proven T1DM and healthy individuals (control group). Body mass index (BMI), fasting blood sugar (FBS), glycated hemoglobulin (HbA1c), thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), thyroid autoantibodies, including anti-thyroid peroxidase (anti-TPO) in addition to anti-thyroglobulin (anti-Tg), and TNF- α concentrations were evaluated in T1DM and control groups. Our findings revealed that thyroid autoantibodies were significantly more prevalent in T1DM patients, elevated TSH, and significantly higher TNF-α levels than in the control group, indicating an increased risk for inflammation based on cytokine levels. The current study proved that in T1DM patients’ sera compared to the healthy control, thyroid autoantibodies and TNF-α levels were positively correlated. In conclusion, poor diabetes management and high TSH levels may indicate subclinical hypothyroidism, which impacts diabetes control. This is possibly linked to thyroid autoimmunity. Future research is needed to understand how TNF- αcontributes to the progression of diabetes disease and its complications.